Peningkatan Jembatan Udara Melalui Angkutan Udara Perintis Kargo Untuk Daya Dukung Ketahanan Nasional - Dandy Nugraha,; Dimas Barazki, Muhammad (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The air bridge is one of the government's flagship programs that plays an important role in reaching underdeveloped, remote, outermost and border areas (3TP). This is an opportunity as well as a challenge so that the air bridge program needs to be improved from the aspect of national resilience, Asta Gatra. This research aims to study the development of the air bridge program through cargo pilot air transport to enhance national resilience. The research methodology used is qualitative with a descriptive approach. The secondary data used is the Decree of the Director General of Civil Aviation Number: PR 24 of 2022. Analysis of Asta Gatra aspects of air bridge implementation at 6 airports for cargo pilot air transport area coordinators consists of 40 flight routes (PP) with 62 flight frequencies per-week. The air bridge programme needs to be thoroughly reviewed to measure the carrying capacity of national resilience so that the implementation of air bridge program in the future can be improved. The results of the study show the importance of air bridges through cargo pilot air transport for the carrying capacity of national resilience, so that the implementation of an effective, efficient, reliable and sustainable air bridge program for underdeveloped, remote, outermost and border areas (3TP) can be realised.